Long non-coding RNA growth arrest specific 5 is downregulated in sepsis-ALI and inhibits apoptosis by up-regulating miR-146a. Issue 2 (1st February 2022) - Li, Jiaqiong; Xu, Hongyang; Li, Na; Du, Wenjing; Ti, Junxiang; Chen, Jingyu
ABSTRACT: Long non-coding RNA (lncRNA) growth arrest specific 5 (GAS5) and microRNA (miR)-146a both have inhibitory effects on LPS-induced inflammation, suggesting the crosstalk between them. In this study, the expression of GAS5 and miR-146a in patients with sepsis-induced acute lung injury (sepsis-ALI), sepsis patients without obvious complications (sepsis) and healthy controls were studied by RT-qPCR. The role of GAS5 in the expression and methylation of miR-146a in human bronchial epithelial cells (HBEpCs) were studied by RT-qPCR and methylation-specific PCR (MSP), respectively. Cell apoptosis was analyzed by flow cytometry. We found that GAS5 and miR-146a were downregulated in sepsis-ALI and the expression of these two were correlated. LPS induced the downregulation of GAS5 and miR-146a in HBEpCs. In HBEpCs, overexpression of GAS5 increased the expression levels of miR-146a and reduced the methylation of miR-146a gene. Under lipopolysaccharide (LPS) treatment, overexpression of GAS5 and miR-146a decreased the apoptotic rate of HBEpCs. Moreover, the combined overexpression of GAS5 and miR-146a showed stronger effects. Therefore, GAS5 is downregulated in sepsis-ALI and inhibits cell apoptosis by up-regulating the expression of miR-146a.